Synergistic toughen epoxy resin by incorporation of polyetherimide and amino groups grafted MWCNTs. (October 2020) - Chen, Zhengguo; Luo, Jie; Huang, Zhuang; Cai, Chaoqian; Tusiime, Rogers; Li, Zhaoyang; Wang, Hengxing; Cheng, Chao; Liu, Yong; Sun, Zeyu; Zhang, Hui; Yu, Jianyong
Abstract: In this work, low content of polyetherimide (PEI) and amino groups grafted MWCNTs (NH2 -MWCNTs) were simultaneously employed in order to toughen epoxy resin without scarifying the thermal properties. The grafted NH2 groups on the surface of MWCNTs leads to outstanding dispersibility. The influence of PEI and NH2 -MWCNTs on the epoxy resin including the curing behaviors, mechanical properties, phase structures, and thermal properties were investigated systematically. The NH2 -MWCNTs/PEI/Epoxy ternary composites with 5 phr (parts per hundred of resin) PEI and 0.4 phr NH2 -MWCNTs shows the maximum value of 73.1%improvement of the fracture toughness in term of K IC compared to that of neat epoxy. A prefer dispersion of NH2 -MWCNTs with PEI microspheres was unambiguously detected from the detailed SEM phase structures, which is most likely associated with the dramatic improvement of the toughness. Thus, an interestingly synergistic toughening effect were obtained through coupling matrix crack bridging, deflection or plastic deformation of PEI microspheres and crack bridging or pulling out of carbon nanotubes. The glass transition temperature of ternary composite material with low content of PEI and NH2 -MWCNTs was significantly increased, and the decomposition initial temperature of the ternary composite material did not sacrifice the thermal stability of the epoxy resin. In addition, the thermal stability of epoxy resin was also slightly improved by incorporation of low content of PEI and NH2 -MWCNTs. Highlights: Low content of Polyetherimide (PEI) and amino groups grafted MWCNTs (NH2 -MWCNTs) were employed to improve not only the toughness, but also the flexural properties and tensile properties of the epoxy resin. The addition of PEI and NH2 -MWCNTs improved not only the toughness, but also the flexural properties of the epoxy resin. A synergistic toughening effect could be clearly observed which included PEI microspheres and NH2 -MWCNTs with the coupling of matrix crack bridging, deflection, or nanotube pulling out. The thermal stability of epoxy resin was also slightly improved by incorporation of low content of PEI and NH2 -MWCNTs.